Characterization of microporous oxide layer synthesized on Ti–6Al–7Nb alloy by micro-arc oxidation - Moskalewicz, T.; Kruk, A.; Kot, M.; Kayali, S.; Czyrska-Filemonowicz, A. (Springer Science and Business Media LLC, 2014)
Abstract In this work a microporous oxide layer was formed on two phase (α+β) Ti–6Al–7Nb titanium alloy by the micro-arc oxidation process in an electrolyte containing (CH 3 COO) 2 CaH 2 O and Na 3 PO 4 . The thickness of the surface layer was in the range of 2.7 μm–3.6 μm. Microstructure of the surface layer and the substrate alloy was characterized with use of scanning- and transmission electron microscopy as well as by X-ray diffractometry. The microstructure of the surface layer consisted of TiO 2 rutile and anatase nanocrystals as well as of amorphous regions containing mainly Ti, Ca and O atoms and a minority of P, Al and Nb ones. The surface layer was highly porous. The open pores, with diameter up to 6 µm, were homogenously distributed in the specimen surface. Electron tomography was used to investigate the pores morphology and spatial distribution. It was found that open pores exhibited a complex geometry. The closed pores had nearly spherical shape. Adhesion of the surface layer to the titanium alloy substrate was investigated by means of the scratch-test. The value of critical load L C2 =14 N indicates a good layer adhesion to the underlying substrate.